Dietary emulsifiers directly alter human microbiota composition and gene expression ex vivo potentiating intestinal inflammation. Issue 8 (21st March 2017) - Chassaing, Benoit; Van de Wiele, Tom; De Bodt, Jana; Marzorati, Massimo; Gewirtz, Andrew T
Abstract : Objective: The intestinal microbiota plays a central role in the development of many chronic inflammatory diseases including IBD and metabolic syndrome. Administration of substances that alter microbiota composition, including the synthetic dietary emulsifiers polysorbate 80 (P80) and carboxymethylcellulose (CMC), can promote such inflammatory disorders. However, that inflammation itself impacts microbiota composition has obfuscated defining the extent to which these compounds or other substances act directly upon the microbiota versus acting on host parameters that promote inflammation, which subsequently reshapes the microbiota. Design: We examined the direct impact of CMC and P80 on the microbiota using the mucosal simulator of the human intestinal microbial ecosystem (M-SHIME) model that maintains a complex stable human microbiota in the absence of a live host. Results: This approach revealed that both P80 and CMC acted directly upon human microbiota to increase its proinflammatory potential, as revealed by increased levels of bioactive flagellin. The CMC-induced increase in flagellin was rapid (1 day) and driven by altered microbiota gene expression. In contrast, the P80-induced flagellin increase occurred more slowly and was closely associated with altered species composition. Transfer of both emulsifier-treated M-SHIME microbiotas to germ-free recipient mice recapitulated many of the host and microbial alterations observed in mice directly treated with emulsifiers. Conclusions: These results demonstrate a novel paradigm of deconstructing host–microbiota interactions and indicate that the microbiota can be directly impacted by these commonly used food additives, in a manner that subsequently drives intestinal inflammation.